OPTIMIZATION OF INTERMEDIATE GRAVITATIONAL FORCES IN THE RESTRICTED THREE-BODY PROBLEM - Eshboev Ilhom Ikrom o‘g‘li (World Scientific Research Journal, 2025)
The restricted three-body problem is a classical and complex challenge in celestial mechanics, involving the motion of a small body under the gravitational influence of two massive primaries. This paper focuses on optimizing the intermediate gravitational forces acting within this system to enhance computational efficiency and trajectory stability. By employing advanced numerical integration techniques and modern optimization algorithms such as genetic algorithms and particle swarm optimization, we explore strategies for minimizing energy expenditure and improving predictive accuracy in orbit calculations. Applications in spacecraft trajectory planning, orbital insertion, and mission design are also discussed. The study contributes to ongoing efforts to model and control chaotic dynamical systems in astrodynamics with greater precision.